Extended Preclinical Safety, Efficacy and Stability Testing of a Live-attenuated Chikungunya Vaccine Candidate. - Kenneth S Plante; Shannan L Rossi; Nicholas A Bergren; Robert L Seymour; Scott C Weaver (Public Library of Science (PLoS), 2015)
We recently described a new, live-attenuated vaccine candidate for chikungunya (CHIK) fever, CHIKV/IRES. This vaccine was shown to be well attenuated, immunogenic and efficacious in protecting against CHIK virus (CHIKV) challenge of mice and nonhuman primates. To further evaluate its preclinical safety, we compared CHIKV/IRES distribution and viral loads in interferon-α/β receptor-incompetent A129 mice to another CHIK vaccine candidate, 181/clone25, which proved highly immunogenic but mildly reactive in human Phase I/II clinical trials. Compared to wild-type CHIK virus, (wt-CHIKV), both vaccines generated lower viral loads in a wide variety of tissues and organs, including the brain and leg muscle, but CHIKV/IRES exhibited marked restrictions in dissemination and viral loads compared to 181/clone25, and was never found outside the blood, spleen and muscle. Unlike wt-CHIKV, which caused disrupted splenic architecture and hepatic lesions, histopathological lesions were not observed in animals infected with either vaccine strain. To examine the stability of attenuation, both vaccines were passaged 5 times intracranially in infant A129 mice, then assessed for changes in virulence by comparing parental and passaged viruses for footpad swelling, weight stability and survival after subcutaneous infection. Whereas strain 181/clone25 p5 underwent a significant increase in virulence as measured by weight loss (from <10% to >30%) and mortality (from 0 to 100%), CHIKV/IRES underwent no detectible change in any measure of virulence (no significant weight loss and no mortality). These data indicate greater nonclinical safety of the CHIKV/IRES vaccine candidate compared to 181/clone25, further supporting its eligibility for human testing.